The Effect Of Tax Planning And Good Corporate Governance On The Market Value Of Banking Companies Listed On The Indonesian Stock Exchange 2022-2024 - Shilfa Yustika Konsesa Shilfa; Srikalimah; Agus Athori (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the effects of Tax Planning and Good Corporate Governance (GCG) on firm value among banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. This research employed a quantitative approach with an explanatory research design. The study population consisted of 47 banking companies, and a total of 141 observations were obtained from the companies' annual reports and financial statements. Data were analyzed using IBM SPSS Statistics through descriptive statistics, classical assumption tests, multiple linear regression analysis, the coefficient of determination, t-tests, and F-tests. The results indicate that Tax Planning has a positive and statistically significant effect on firm value, with a significance value of 0.009, while Good Corporate Governance also has a positive and statistically significant effect on firm value, with a significance value of 0.038. Furthermore, the simultaneous test demonstrates that Tax Planning and Good Corporate Governance jointly have a significant effect on firm value, as indicated by an F-test significance value of 0.006. The Adjusted R-squared value of 0.065 indicates that the two independent variables explain 6.5% of the variation in firm value. These findings suggest that the implementation of effective tax planning strategies and sound corporate governance practices can enhance firm value and strengthen investor confidence in the banking sector